Synthesis and characterization of hypercrosslinked polymer : effect of reaction time - Noor Syahirah, Othman (2015)
Hypercrosslinked polymers were categorized as one of the new generation of the porous polymers. The interest in hypercrosslinked polymer is growing rapidly due to their unique physical, chemical and potential applications in many fields from drug-delivery to coatings. In this research, non-aqueous dispersion polymerization precursor was used prior to hypercrosslinking reaction in order to obtain hypercrosslinked polymer and it is focus on the effect of reaction time on the morphology of hypercrosslinked polymer. Hypercrosslinked particles were prepared in post-polymerization using the Friedel-Craft reaction that was swollen in anhydrous 1, 2-dichloroethane (DCE). Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and Thermal Gravimetry Analyzer (TGA) were used to characterize the hypercrosslinked particles. The results show that before post-polymerization, the precursor display good quality monodisperse spherical. However, after hypercrosslinking reaction, the quality of final product decrease which is for 12 hours and 24 hours of reaction time, hypercrosslinked particles were agglomerated but for 18 hours of reaction time, the particles can retain their quality similar with quality of precursor. For FTIR analysis, sample of 18 hours, 12 hours and 24 hours showed aliphatic CI streching vibrations at 1290 cm-1 ascribed to chloromethyl group derived from VBC residues and for TGA results, samples of 18 hours, 12 hours and 24 have the maximum weight loss with the compositions about 66.11 %, 47.07 % and 39.96 % respectively. Sample of 18 hours has the highest reaction interval compared with the other.